Machine learning improves prediction of delayed cerebral ischemia in patients with subarachnoid hemorrhage. (10th November 2018) - Ramos, Lucas Alexandre; van der Steen, Wessel E; Sales Barros, Renan; Majoie, Charles B L M; van den Berg, Rene; Verbaan, Dagmar; Vandertop, W Peter; Zijlstra, I Jsbrand Andreas Jan; Zwinderman, A H; Strijkers, Gustav J; Olabarriaga, Silvia Delgado; Marquering, Henk A
Abstract : Background and purpose: Delayed cerebral ischemia (DCI) is a severe complication in patients with aneurysmal subarachnoid hemorrhage. Several associated predictors have been previously identified. However, their predictive value is generally low. We hypothesize that Machine Learning (ML) algorithms for the prediction of DCI using a combination of clinical and image data lead to higher predictive accuracy than previously applied logistic regressions. Materials and methods: Clinical and baseline CT image data from 317 patients with aneurysmal subarachnoid hemorrhage were included. Three types of analysis were performed to predict DCI. First, the prognostic value of known predictors was assessed with logistic regression models. Second, ML models were created using all clinical variables. Third, image features were extracted from the CT images using an auto-encoder and combined with clinical data to create ML models. Accuracy was evaluated based on the area under the curve (AUC), sensitivity and specificity with 95% CI. Results: The best AUC of the logistic regression models for known predictors was 0.63 (95% CI 0.62 to 0.63). For the ML algorithms with clinical data there was a small but statistically significant improvement in the AUC to 0.68 (95% CI 0.65 to 0.69). Notably, aneurysm width and height were included in many of the ML models. The AUC was highest for ML models that also included image features: 0.74 (95% CI 0.72 to 0.75). Conclusion: ML algorithms significantly improve the prediction of DCI in patients with aneurysmal subarachnoid hemorrhage, particularly when image features are also included. Our experiments suggest that aneurysm characteristics are also associated with the development of DCI.